2021
DOI: 10.3390/ijerph18041764
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Worldwide Trends on Energy Poverty Research: A Bibliometric Analysis (1999–2019)

Abstract: Energy poverty is one of the main challenges facing humanity in the 21st century. Research on energy poverty is becoming a common focus of scholars in many areas. Bibliometrics can help researchers dig deep into the information of specific research fields from a quantitative perspective. In this study, we collected 1018 research papers in the field of energy poverty published in the period 1999–2019 from the Web of Science databases and conducted a bibliometric analysis on them. Cleaning and screening of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…A mapping of a 21st-century problem, poverty energy, was proposed by [23]. Thus, a bibliometric analysis was made using the Web of Science database, and for the 1999-2019 temporal sample, they obtained 1018 articles in the sample.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A mapping of a 21st-century problem, poverty energy, was proposed by [23]. Thus, a bibliometric analysis was made using the Web of Science database, and for the 1999-2019 temporal sample, they obtained 1018 articles in the sample.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the periods, Energy Policy publishes on the subject for the longest period, while Renewable and Sustainable Energy Reviews publishes the studies with greater influence; Sovacool is the researcher with the highest number of publications and the most influential. Finally, the authors highlighted four areas that should be research trend in the coming years: energy poverty in developing countries, impacts of energy poverty on vulnerable groups, root causes of energy poverty and consequences of emission reduction policies [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the energy poverty research field has grown significantly, almost exponentially in the last decade [15,16], and significant advances to the original conceptualization of the phenomenon have been made, there is still significant theoretical and methodological divergence in the literature. Moreover, many politicians and policy-makers (and some researchers) still have an antiquated and oversimplified definition of the phenomenon, far away from recent advances.…”
Section: Introductionmentioning
confidence: 99%
“…They identified several clusters of authors, keywords, institutions, bibliographic coupling etc., though they described them superficially without deepening into the theoretical implications of the analysis. Xiao et al [16] pursued mapping the trends in energy poverty research in the period 1999-2019 by the analysis of 1026 WoS documents with the search keywords of fuel/energy poor and fuel/energy poverty. Their study confirmed the interdisciplinary nature of the research field.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical tools, including R-bibliometrix, VOSviewer, CiteSpace, BICOMB, and BibExcel, are integrated as an automatic workflow to carry out multistep bibliometric analyses. In prior studies, bibliometric analysis has been successfully performed in various disciplines, especially in environmental science and medicine ( 29 ).…”
Section: Introductionmentioning
confidence: 99%